Analisis Hubungan Pengetahuan dan Sikap Terhadap Perilaku Pencegahan Demam Berdarah Dengue - hadianti, elsa; Indah Sri Wahyuningsih (STIKes Ibnu Sina Ajibarang, 2025)
Dengue Hemorrhagic Fever (DHF) has become an increasingly serious public health issue, with the number of patients continuously increasing year by year and its spread becoming more widespread. To break the chain of transmission, DHF prevention strategies play a crucial role. Currently, low community participation in DHF prevention programs through the 3M Plus approach remains a major obstacle, caused by several factors including predisposing factors such as knowledge, attitudes, beliefs, and values; enabling factors such as physical environmental conditions and availability of facilities and infrastructure; and reinforcing factors in the form of healthcare workers' roles. This study aims to analyze the relationship between knowledge and attitudes with DHF prevention behavior. The research was conducted using an analytical approach with a cross-sectional design. The research population consisted of all household heads who permanently reside in RT 03 RW 01 Alam Jaya Village, totaling 76 respondents. The sampling technique applied was total sampling namely 76 respondents. Data analysis used the chi-square test with a significance level of 5%. Based on research findings, no relationship was found between knowledge and DHF prevention behavior (p-value = 0.659) nor between attitudes and DHF prevention behavior (p-value = 0.846). The main conclusion of this study states that there is no correlation between knowledge and attitudes with DHF prevention behavior. Therefore, it is recommended that future research explore other factors that influence DHF prevention behavior.